Fabricação de compósitos e ensaios de absorção de água para aplicações em embarcações - Aguiar, Lituan Lamarck Soares (Universidade Federal Rural do Semi-Árido, 2018)
The search for alternative materials that can partially or totally replace traditional materials is increasing. Due to this it was necessary to develop studies that eventually led to the discovery of a new type of material, which is the composite. A composite is the joining of two or more materials into distinct layers. In this way allowing the creation of another that has characteristics. Which their constituents could not provide separately. A type of composite widely used is the one manufactured with a polymeric matrix and reinforcement of synthetic fiber of glass, being used in several areas for repair or even construction of objects. The naval area is increasingly using this type of material because it has better mechanical characteristics than many materials because it has fiberglass. Due to the environments to which they are exposed and to the efforts they undergo, it is necessary to perform tests to verify if the composite to be used has the necessary characteristics for the project to be developed, such as small boat manufacturing. carried out a study on composites and their manufacture, as well as performing the water absorption test. The process used was hand lay-up, through which composites with various configurations were made: polyester resin polymer, a composite with two layers of fiberglass mat, another composite with two layers of mat and one of fabric, and a composite with three layers of blanket. These were submitted to the water absorption test with common water, distilled water and sea water, to observe their behavior in each of them. Thus it was possible to determine that the composite with three layers of manta had the best performance in the resistance to water absorption, followed by the reinforcement of two blankets, soon after, consisting of two blankets and one layer of fabric. The resin-only polymer was the most resistant to water absorption, but it is a very fragile material and is not usual for boats. In addition, it was possible to compare the results obtained with other works already published.
Monografia
Keywords: Compósito; Laminação; Vidro; Material; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA